A novel multi-flapping-wing air vehicle: conceptual design and aerodynamic analysis - Billingsley, Ethan; Ghommem, Mehdi; Vasconcellos, Rui [UNESP]; Abdelkefi, Abdessattar (American Institute of Aeronautics and Astronautics (AIAA), 2022)
Many designs for flapping-wing vehicles have been inspired from birds given their outstanding flight capabilities. Birds have been observed to obtain aerodynamic benefits by flying together in V-formation, a unique feature which up to this point has not been incorporated in the design of a flapping-wing drone. Therefore, the goal of this work is to propose a novel design for a multi-flapping-wing drone (MFWD) which uses a V-shape arrangement of flapping wings in order to enhance its propulsive efficiency and lift production. In this work, sizing and weight estimation for a MFWD are conducted following the establishment of a mission plan. Aerodynamic simulations are generated to select the appropriate wing shape and airfoil section to satisfy the design requirements of the proposed drone. Then, a stability analysis is carried out to determine the relative position of the aerodynamic center with respect to the center of gravity. Subsequently, a tail sizing procedure is performed based on the calculated length of the tail arm identified from the stability analysis, and a flapping mechanism is designed based on a common configuration reported in the literature. Finally, a CAD model of the MFWD conceptual design is presented and discussed.